INTERNET OF THINGS (IoT) TRAINING FOR STUDENTS OF SMK NEGERI 1 TANJUNG SARI, LAMPUNG SELATAN - Akhmad Jayadi; Jaka Persada Sembiring; Novia Utami Putri; Qadhli Jafar Adrian; I Wayan Sudana; Fajar Anggit Nugroho; Okky Adi Darmawan; Nur Faqih Ardiantoro (Universitas Teknokrat Indonesia, 2022)
Internet of Things (IoT) is a technology that is currently busy been discussed recently. With this technology, every device we use have later can be connected to the internet, so it can be controlled from remotely with a smartphone or even with voice commands. As in our homes, there will be many items that are connected by the internet of things, such as refrigerators, lights, tv, house doors and other items. We can control it with our smartphone. This IoT works using relays and NodeMCU as a code store that has been created in the Arduino ide software.